The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.5194/npg-25-731-2018
|View full text |Cite
|
Sign up to set email alerts
|

Application of ensemble transform data assimilation methods for parameter estimation in reservoir modeling

Abstract: Over the years data assimilation methods have been developed to obtain estimations of uncertain model parameters by taking into account a few observations of a model state. The most reliable methods of MCMC are computationally expensive. Sequential ensemble methods such as ensemble Kalman filers and particle filters provide a favourable alternative. However, Ensemble Kalman Filter has an assumption of Gaussianity. Ensemble Transform Particle Filter does not have this assumption and has proven to be highly bene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…1 a and b and as it has been reported in the literature, e.g. [28,29]. When uncertainty is in both permeability and boundary conditions, we investigate methods performance for two numerical setups.…”
Section: Data Assimilation Without Localizationmentioning
confidence: 94%
See 3 more Smart Citations
“…1 a and b and as it has been reported in the literature, e.g. [28,29]. When uncertainty is in both permeability and boundary conditions, we investigate methods performance for two numerical setups.…”
Section: Data Assimilation Without Localizationmentioning
confidence: 94%
“…Hence, one has to decrease the number of degrees of freedom, i.e. by distancebased localization of [27,28] abbreviated here LETPF. Assume we have a numerical grid of N × N size with grid cells denoted by X l for l = 1, .…”
Section: Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…It also has a localized version. In [26], we have employed the method to an inverse problem of uncertain permeability. We have shown that though localization makes the ensemble transform particle filter deteriorate a posterior estimation of the leading modes, it makes the method applicable to high-dimensional problems.…”
Section: Introductionmentioning
confidence: 99%